Yevropa NATOvskoy konstruktsii iz pentagonovskoy prduktsii - Kukryniksy (Плакат СССР (Plakat), 1981)
City constructed entirely of nuclear missiles as family flees and general signals halt. Helicopters patrol the sky Original title: Европа НАТОвской конструкции из пентагоновской прдукции PO-0336